A systematic analysis of a two-word concgram in Nepalese policy documents: A corpus-driven approach - Bastola, Madhu Neupane (Journal of NELTA, 2019)
Corpus linguistics can inform language teaching in various aspects from syllabus designing to creating exercises based on the real use of language. However, its use in language teaching is still rare. In the context of Nepal, though corpus linguistics forms a part of the University Curriculum in English Education, the students are rarely offered a practical experience of corpus analysis. The same is the case with teacher training courses. This paper followed an analytical procedure for identifying phraseological variation within a two-word ‘concgram’ that is a set of co-occurring words. In this paper, a two-word concgram, make/effort, is analyzed to identify concgram configurations, the most frequently used form, and its meaning by using concordance lines. Lastly, the paper presents the implications of corpus analysis in English language teaching.